Primary Education In Improving Quality Efficiency Modern Approach - Khakimova Nargiza Boxodirovna (Peerian Journals Publishing, 2023)
In this article, primary education in improving quality efficiency information was provided about the modern approach, integration of Technology, Project-Based Training, personalized learning.
Keywords: elementary education; modern world